A Case of Tracheal Hamartoma Resected with Loop Electrocautery - Marios Panagiotou; Alexandros Kalkanis; Napoleon Karagiannidis; Vlasis Polychronopoulos (Case Reports in Pulmonology)
The authors report on the case of a 67-year-old man with longstanding breathlessness, which was eventually attributed to a fixed mass in the upper third of the trachea causing upper airway obstruction. The lesion was amenable to loop electrocautery resection via flexible bronchoscopy that led to prompt resolution of patient symptoms. Biopsy was consistent with tracheal hamartoma, an exceedingly rare benign tracheal tumor. All the cases of tracheal hamartomas in the literature to date, the application of electrocautery and other methods of interventional bronchoscopy for resection of selected tracheal tumors are discussed.